Trophic Requirements of the Sea Urchin Paracentrotus lividus Varies at Different Life Stages: Comprehension of Species Ecology and Implications for Effective Feeding Formulations - Grosso, Luca; Rakaj, Arnold; Fianchini, Alessandra; Tancioni, Lorenzo; Vizzini, Salvatrice; Boudouresque, Charles-François; Scardi, Michele (Frontiers in Marine Science, 2022)
Investigations on trophic requirements of different life cycle stages of Paracentrotus lividus are crucial for the comprehension of species ecology and for its artificial rearing. The future success of echinoculture depends heavily on the development of suitable and cost-effective diets that are specifically designed to maximize somatic growth during the early life stages and gonadal production in the later stages. In this context, a considerable number of studies have recommended animal sources as supplements in sea urchin diets. However, with the exception of Fernandez and Boudouresque (2000), no studies have investigated the dietary requirements over the different life stages of the sea urchin. In the present study, the growth and nutrition of three life stages of P. lividus (juveniles: 15-25 mm; subadults: 25-35 mm; adults: 45-55 mm) were analyzed over a 4-month rearing experiment. Three experimental diets, with 0%, 20% and 40% of animal sourced enrichments, were tested in parallel in sea urchin three size classes. The food conversion ratio, somatic and gonadal growth were assessed in each condition in order to evaluate the optimal level of animal-sourced supplements for each life stage. A general growth model covering the full post-metamorphic P. lividus life cycle was defined for each condition. During the juvenile stage P. lividus requires higher animal supply (40%), while a feeding requirement shift takes place toward lower animal supply (20%) in sub-adult and adult stages. Our results evidenced that the progressive increase in size after the metamorphosis led to a consequent variation of trophic requirements and food energy allocation in the sea urchin P. lividus. Macronutrient requirements varied widely during the different life stages, in response to changes in the energy allocation from somatic growth to reproductive investment. This study sheds light on P. lividus trophic ecology, broadening our basic knowledge of the dietary requirements of juveniles, sub-adults and adults as a function of their behavior also in the natural environment.